Assessment of exposure to metalworking fluids and respiratory health allergies among machining industry workers in Selangor, Malaysia - Liaw, Soo Hui (2015)
Metal machining processes such as cutting, turning, machining, grinding, milling and drilling require lubrication and dispersal of heat generated. Major chemicals used in machining industry include metalworking fluids (MWFs).posure to MWFs are associated with various types of respiratory and healtngor. The study design was a cross-sectional comparative study. The workers were purposely sampled from the staff list and classified into the MWFs exposed group who consisted of machining and stamping workers while the unexposed group consisted of assembly and administrative workers. The types and uses of metalworking fluids, respiratory and allergy symptoms were obtained through questionnaire interviews. Personal air samples were collected to assess the chromium and aluminum of the MWFs. Blood samples were collected for total immunoglobulin E (TIgE) analysis as indicator of respiratory allergy. The lung function tests were carried out at the beginning (pre-shift) and at the end of work (post-shift) using Spirolab II model spirometer to assess the cross-shift lung function capacity. This study showed that the MWFs unexposed group had significantly higher TWA8 airborne aluminum concentration (median=0.24 μg/m3) than the exposed group (median=0.13 μg/m3) (p=0.027). Further analysis showed this was contributed from warehouse workers and quality control (QC) workers. Findings showed significantly higher cough symptom (19.6%) (p=0.036), morning coughwith sputum (3.9%) (p=0.021), skin itchiness (10.5%) (p=0.014) and high,serum total IgE (54.3%) (p=0.004) among the MWFs exposed group than the unexposed group. The uses of MWFs were significantly associated with higher risk of skin itchiness (OR 4.82, CI 1.54-15.16). Skin itchiness was significantly higher with the use of soluble oil (OR 7.48, CI 1.97-28.38) followed by stamping Oil (OR 5.10, CI 1.33-19.61). Further analysis based on operation showed the machining workers reported significantly higher risk of cough symptom (OR 2.54, CI 1.18-5.47) and Grade 1 Dyspnea (OR 2.28, CI 1.00-5.16) than the administrative workers. The cough symptom was significantly associated with the use of straight oil. Our study results showed the presence of respiratory and allergy risks among workers in the machining industry. Findings showed significantly higher TWA8 airborne aluminum among the MWFs unexposed group suggested the management might need to review the structure design and current location of the warehouse and quality control offices as it is currently located with close proximity to its production line. Our study findings revealed and elevated risk of skin itchiness among exposed group associated with the use of soluble and stamping oil. The cough symptom was significantly associated with the use of straight oil. This suggested the management and future study shall examine the effectiveness of ventilation system and the use of personal protective equipment or clothing when working with different types of MWFs.